2022
DOI: 10.1186/s12913-022-08006-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic assessment of incorporating the hexavalent vaccine as part of the National Immunization Program of Peru

Abstract: Background This study aimed to estimate the economic impact of replacing the current Peruvian primary immunization scheme for infants under 1 year old with an alternative scheme with similar efficacy, based on a hexavalent vaccine. Methods A cost-minimization analysis compared the costs associated with vaccine administration, adverse reactions medical treatment, logistical activities, and indirect social costs associated with time spent by parents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The study supported the advantages of fully liquid vaccines over reconstituted vaccines having the potential of cost savings by shortening vaccine preparation time and reducing the risk of vaccination error [19]. Similar results were seen when introducing the ready-to-use hexavalent vaccine into the national vaccination program in Peru that reduce total costs due to lower time costs despite an increase in vaccine costs [21]. A similar cost analysis was also performed for the DTaP-based hexavalent vaccine (DTaP-292 IPV-Hib-HepB) in Malaysia.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The study supported the advantages of fully liquid vaccines over reconstituted vaccines having the potential of cost savings by shortening vaccine preparation time and reducing the risk of vaccination error [19]. Similar results were seen when introducing the ready-to-use hexavalent vaccine into the national vaccination program in Peru that reduce total costs due to lower time costs despite an increase in vaccine costs [21]. A similar cost analysis was also performed for the DTaP-based hexavalent vaccine (DTaP-292 IPV-Hib-HepB) in Malaysia.…”
Section: Discussionsupporting
confidence: 72%
“…These findings were the incentives to investigate more in depth the rates of infection of pentavalent vaccines to be reconstituted versus the hexavalent vaccine that is ready to be used and estimate their cost difference. Studies on the economic value of the hexavalent vaccine suggested the following costs to be assessed: cost of the vaccine, cost of inpatient and/or outpatient visits, delivery cost, time cost, labor cost, cost for immunization errors and adverse events, and waste cost [ 18 , 19 , 20 , 21 ]. Our study adds the cost of infection contamination following immunization using the results of a model construct.…”
Section: Introductionmentioning
confidence: 99%
“…These higher-valent pediatric combination vaccines have demonstrated many advantages over monovalent, bivalent, and trivalent vaccines. Tetravalent, pentavalent, and hexavalent vaccines improve compliance and timeliness of vaccination [ 2 ], reduce healthcare professionals’ workloads [ 3 ] and risk of needlestick injuries [ 4 ], decrease the number of injections to save space for more new antigens in vaccination schedule, simplify immunization procedures [ 5 ], increase vaccination coverage [ 6 ], and minimize healthcare expenditures [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Switching to the hexavalent vaccine would be expected to simplify logistics and associated delivery infrastructure, reduce the number of injections and side effects, as well as minimize administration error which may result in better acceptability, convenience and compliance, and ultimately improved vaccination coverage [ 13 ]. Previous studies assessing the potential economic impact of introducing the hexavalent vaccine in the national childhood vaccination programs of Peru, Colombia, and Chile suggest that it would lead to additional acquisition costs, which are partial mitigated by improved logistics, and reduced incidence of adverse events [ 14 16 ]. Here, we assessed the differences in cost from switching from the current childhood primary and booster vaccination schedule with the pentavalent vaccine plus IPV (DTwP-Hib-HB plus IPV) to an alternative series with the hexavalent vaccine (DTaP-Hib-HB-IPV) in Argentina, assuming similar levels of effectiveness across the six biologicals of the vaccine.…”
Section: Introductionmentioning
confidence: 99%